Prothrombin time and Activated Partial Thromboplastin time in Pregnant Women in Southern Nigeria - Avwioro OG, Ezeobi JO, Oduola T, Fakunle OO (Journal of Applied Pharmaceutical Science, 2013)
The incidence of bleeding during and after child birth has become an issue of concern in maternal health. Prothrombin time and activated partial thromboplastin time in antenatal women in the three trimesters were studied in Southern Nigeria. 120 subjects were recruited for the study, consisting of 30 pregnant women each at first, second and third trimesters and 30 non pregnant women as the control. The tests were carried out using standard techniques. The result of the PT showed no statistically significant (P>0.05) difference in the first and third trimesters except in the second trimester (P
Keywords: Prothrombin time, activated partial thromboplastin t